Challenges and Successes of Women’s Leadership in Higher Education in Qatar: The Case of the Community College of Qatar - Amna Ahmed Obeid Abdelnur; Diana J. Fox (WISE Pendidikan Indonesia, 2026)
This case study examines the cultural, institutional, and personal challenges experienced by women in academic leadership positions at the Community College of Qatar (CCQ), as well as their achievements and perceptions of leadership. Using a mixed-methods approach, data were collected from 26 women holding various leadership positions through a questionnaire, followed by a focus group discussion involving five participants. The findings reveal opportunities and barriers to attaining leadership positions, shaped by workplace culture, professional networks, cultural stereotypes, and domestic responsibilities. Women leaders also experienced burnout, stress, and anxiety after assuming leadership roles. Nevertheless, participants demonstrated strong decision-making skills, resilience, innovation, and collaborative leadership. They contributed to institutional governance by guiding their teams, supporting colleagues, making important decisions, and promoting an inclusive culture that challenges gendered assumptions about leadership. Support from coworkers, families, mentors, institutions, and communities helped participants balance professional and personal responsibilities and overcome cultural and workplace pressures. Appropriate policies, resources, mentoring, and institutional support systems were identified as essential to their success. Although limited in scope, this study contributes to the literature by documenting women’s lived experiences and recommending interventions to address persistent barriers and strengthen women’s leadership in higher education.